Construction and application of multi-party trust mechanism for cross border data flow based on smart contracts - JIANG Rong; HOU Shiping; LUO Shengmei (大数据)
In the context of globalization of the digital economy, cross border data flows face practical challenges such as compliance conflicts caused by legal differences, lack of trust among multiple parties, and difficulties in regulatory audits. This paper proposes a multi-party mutual trust mechanism for cross border data flows based on smart contracts, elaborating from four aspects: core elements of multi-party mutual mechanism, key data structures, business processes, and system architecture. Leveraging the decentralized and tamper proof nature of blockchain, it constructs a full process solution covering identity verification, compliance review, and responsibility tracing. This mechanism effectively addresses the risks of third-party trust dependency and regulatory lag in traditional models. By using technical means to transform compliance requirements into automated execution logic, it enhances the transparency and security of data flows.